Neutrinos in anomaly mediated supersymmetry breaking with R-parity violation - De Campos, F. [UNESP]; Díaz, M. A.; Éboli, O. J.P.; Lineros, R. A.; Magro, M. B.; Mercadante, P. G. (American Physical Society (APS), 2005)
We show that a supersymmetric standard model exhibiting anomaly mediated supersymmetry breaking can generate naturally the observed neutrino mass spectrum as well mixings when we include bilinear R-parity violation interactions. In this model, one of the neutrinos gets its mass due to the tree-level mixing with the neutralinos induced by the R-parity violating interactions while the other two neutrinos acquire their masses due to radiative corrections. One interesting feature of this scenario is that the lightest supersymmetric particle is unstable and its decay can be observed at high energy colliders, providing a falsifiable test of the model. © 2005 The American Physical Society.